FDEM numerical simulation of size effect on mechanical properties of basalts with hidden microcracks - Yi Enbing (Scientific Reports)
Abstract As an important geological environment medium for engineering construction in southwest China, basalt generally contains hidden microcracks at a micro-scale, which leads to significant size effect on its mechanical properties, and relevant research is lacking and unsystematic. A synthetic rock mass model based on the combination of a micro-discrete fracture network method and a finite-discrete element method is used to systematically explore the size effect of the mechanical properties of basalt rock blocks with hidden microcracks. The results showed that: (1) the fracture angle is uniformly distributed, and the fracture length conforms to the logarithmic normal distribution, with an areal fracture intensity P20 of 0.00025/mm2 and P21 of 0.012 mm/mm2. (2) According to the variation trends of mechanical parameters with the increase in the specimen dimension, the REV size of basalt rock blocks with hidden microcracks is determined to be 0.5 m. The mechanical properties obtained at this size are considered equivalent continuum properties and could be used as input parameters of rock blocks in complete rock mass or jointed rock mass for the numerical analysis at an engineering scale. (3) With the increase in the sample dimension, basalt changes from a small-sized complete sample to a medium-sized sample with local defects and then to an REV-sized sample with sufficient defects, the stress–strain curve characteristics under Brazilian disc splitting change from a single-peak shape to a zigzag shape and then to a multi-peak shape, and the failure modes changes from a single-center splitting failure mode to a local structure-controlled failure mode and then to a multi-center splitting failure mode, with the gradual decrease in the brittleness degree. The research results further enrich and improve the basic theory and technical methods of multi-scale analysis of geotechnical engineering, and provide strong scientific and technological support for the safety construction of deep engineering.